Diversity of ginger cultivation in India - a GIS study - K Jayarajan, M S Madan, P Utpala, A K Johny, V A Parthasarathy, (Journal of Spices and Aromatic Crops, 2006)
The climatic conditions of important ginger (Zingiber officinale) growing states of India wereanalysed with the help of Geographic Information System (GIS). The Eco-crop model ofDIVA-GIS indicated that Orissa, West Bengal, north eastern States and Kerala are environ-mentally most suitable for ginger cultivation.